2018
DOI: 10.1038/nrc.2018.6
|View full text |Cite
|
Sign up to set email alerts
|

Using immunotherapy to boost the abscopal effect

Abstract: More than 60 years ago, the effect whereby radiotherapy at one site may lead to regression of metastatic cancer at distant sites that are not irradiated was described and called the abscopal effect (from ‘ab scopus’, that is, away from the target). The abscopal effect has been connected to mechanisms involving the immune system. However, the effect is rare because at the time of treatment, established immune-tolerance mechanisms may hamper the development of sufficiently robust abscopal responses. Today, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
705
1
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 900 publications
(774 citation statements)
references
References 107 publications
8
705
1
11
Order By: Relevance
“…Antigen‐presenting cells, such as macrophages, process these antigens and dendritic cells, through which tumor‐specific cytotoxic T lymphocytes (CTLs) are activated, migrate throughout the body, and find and attack cancer cells other than those that were directly irradiated. However, an increase in the total number of CTLs alone is not regarded as activation of cancer immunity . Because activation cannot be shown without an increase in tumor‐specific CTLs killing cancer cells, Suzuki et al suggested that the presence of an abscopal effect could be indirectly demonstrated by determining the number of tumor‐specific CTLs in the blood before and after irradiation, and observing an increase in the number of lymphocytes attacking cancer only .…”
Section: Discussionmentioning
confidence: 99%
“…Antigen‐presenting cells, such as macrophages, process these antigens and dendritic cells, through which tumor‐specific cytotoxic T lymphocytes (CTLs) are activated, migrate throughout the body, and find and attack cancer cells other than those that were directly irradiated. However, an increase in the total number of CTLs alone is not regarded as activation of cancer immunity . Because activation cannot be shown without an increase in tumor‐specific CTLs killing cancer cells, Suzuki et al suggested that the presence of an abscopal effect could be indirectly demonstrated by determining the number of tumor‐specific CTLs in the blood before and after irradiation, and observing an increase in the number of lymphocytes attacking cancer only .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure , the tumor antigens freshly released after chemotherapy (such as using oxaliplatin, mitoxanthrone, or doxorubicin), phototherapy, or radiotherapy can be utilized as anticancer vaccines in situ to render immunogenic cancer cell death, recruit APCs, and facilitate their maturation . These dying tumor cells elicit the systemic immunity and are capable of long‐term regressing distant untreated tumors . This has been demonstrated with mPEG‐PLGA nanoplatform containing oxaliplatin and gemcitabine, an ICD and a non‐ICD inducer, respectively .…”
Section: Delivery System For Provoking Antitumor Immunitymentioning
confidence: 99%
“…The abscopal effect describes the phenomenon through which radiotherapy to one site of disease can lead to regression of lesions at distant sites. It is proposed that combining immunotherapy with radiotherapy could therefore augment the abscopal effect . In addition, as radiation causes immunogenic cell death, it is proposed that radiation treatment can augment immune checkpoint blockade.…”
Section: Resultsmentioning
confidence: 99%